1999
DOI: 10.1038/sj.bmt.1701752
|View full text |Cite
|
Sign up to set email alerts
|

Pilocarpine hydrochloride relieves xerostomia in chronic graft-versus-host disease: a sialometrical study

Abstract: Summary:Bone marrow transplantation is considered to be the treatment of choice for various hematological and solid malignancies, as well as for bone marrow failure syndromes and some genetic diseases. Unfortunately, a great number of patients who receive allogeneic BMT suffer from graft-versus-host disease (GVHD) following the procedure. Xerostomia is considered to be one of the most annoying complications of chronic GVHD (cGVHD), and the rapidly growing number of BMT patients with prolonged survival renders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 20 publications
1
47
0
1
Order By: Relevance
“…It seems that pilocarpine may increase the output of saliva composition. Consistent with others 3,4,19,26 our study may indicate that pilocarpine normalizes salivary flow and composition alteration in cGVHD patients.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It seems that pilocarpine may increase the output of saliva composition. Consistent with others 3,4,19,26 our study may indicate that pilocarpine normalizes salivary flow and composition alteration in cGVHD patients.…”
Section: Discussionsupporting
confidence: 80%
“…Any increase in salivation, no matter how small, which is accompanied by an increase in the production of beneficial constituents, may be a benefit to patients with xerostomia. 3,4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilocarpine hydrochloride, a nonspecific muscarinic and weak b-adrenergic agonist, 99 was the first drug approved in the United States to be shown to increase salivary flow rates under both resting and stimulated conditions compared with baseline (standard dosing of 5 mg 3 times a day). 103 However, there have been mixed results reported for the administration of pilocarpine during RT as a preventive agent. 79,104,105 Cevimeline is a selective M3 muscarinic receptor acetylcholine analog that when administered orally at a dose of 30 mg given 3 times daily has been shown to increase nonstimulated salivary flow.…”
Section: Palliation and Supportive Care For Patients With Xerostomiamentioning
confidence: 99%
“…The results showed that pilocarpine is superior to placebo to relieve xerostomia complaints. At the present time it has been well established that oral pilocarpine is able to improve sicca symptoms, in particular those related to eyes and mouth in patients with systemic disorders such as Sjögrens syndrome (22)(23)(24) or other autoimmune conditions (25) and secondary to radiation therapy (26). After oral administration, the most common side effect is sweating, but urinary and gastrointestinal disturbances are also frequently reported (3,6,22).…”
Section: Introductionmentioning
confidence: 99%